Large-scale synchronized activity in the embryonic brainstem and spinal cord - Momose-Sato, Yoko; Sato, Katsushige (Frontiers in Cellular Neuroscience, 2013)
In the developing central nervous system, spontaneous activity appears well before the brain responds to external sensory inputs. One of the earliest activities is observed in the hindbrain and spinal cord, which is detected as rhythmic electrical discharges of cranial and spinal motoneurons or oscillations of Ca2+- and voltage-related optical signals. Shortly after the initial expression, the spontaneous activity appearing in the hindbrain and spinal cord exhibits a large-scale correlated wave that propagates over a wide region of the central nervous system, maximally extending to the lumbosacral cord and to the forebrain. In this review, we describe several aspects of this synchronized activity by focusing on the basic properties, development, origin, propagation pattern, pharmacological characteristics, and possible mechanisms underlying the generation of the activity. These profiles differ from those of the respiratory and locomotion pattern generators observed in the mature brainstem and spinal cord, suggesting that the wave is primordial activity that appears during a specific period of embryonic development and plays some important roles in the development of the central nervous system.